Inspiring an Early Passion for Science: The Impact of Hands-on Activities on Children's Motivation - Melek Merve Yilmaz; Asli Bekirler; Ayperi Dikici Sigirtmac (ECNU Review of Education)
Purpose The aim of this research is to determine the impact of hands-on science activities on preschool children's motivation for science. Design/Approach/Methods The study group of the research, in which the quasi-experimental design with pretest–posttest control group was used, consists of 25 children aged 60–72 months who are continuing their preschool education. While the experimental group implemented hands-on science activities, the control group continued with the regular preschool education program. Science Motivation Scale for Preschool Children was used as a data collection tool. In the analysis of the data, independent samples t -test, Mann–Whitney U test, and Wilcoxon signed-rank test were used. Findings Within the scope of the research, it was concluded that science activities based on hands-on activities were effective in increasing children's science motivation. In addition, it was observed that science motivation did not differ according to gender, and there was an increase in the science motivation of both girls and boys in the experimental group. Originality/Value The results obtained from the study show that children's science motivation can be shaped through hands-on activities.